2006
DOI: 10.1155/mi/2006/97257
|View full text |Cite
|
Sign up to set email alerts
|

Similar Effects of General and Spinal Anaesthesia onPerioperative Stress Response in Patients Undergoing Haemorrhoidectomy

Abstract: Surgery induces release of neuroendocrine hormones (cortisol), cytokines (interleukin-6: IL-6, tumour necrosis factor-α: TNF-α), acute phase proteins (C-reactive protein: CRP, leptin). We studied the effects of general and spinal anaesthesia on stress response to haemorrhoidectomy. Patients were assigned to general and spinal anaesthesia groups (n = 7). Blood samples were drawn before induction and 24 hours after surgery. Perioperative levels of IL-6, TNF-α, CRP, cortisol, and leptin were comparable among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 23 publications
0
17
0
8
Order By: Relevance
“…Furthermore, the role of ropivacaine on the inflammatory response following surgical trauma is still unclear. The levels of certain pro-inflammatory cytokines, that is, interleukin-6 (IL-6) and tumor necrosis factor alpha (TNF-α) have been previously investigated after anesthesia in surgical patients [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the role of ropivacaine on the inflammatory response following surgical trauma is still unclear. The levels of certain pro-inflammatory cytokines, that is, interleukin-6 (IL-6) and tumor necrosis factor alpha (TNF-α) have been previously investigated after anesthesia in surgical patients [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…8 The perioperative changes of serum TNF-a and IL-6 and the effects of different anesthetic techniques have been investigated in surgical patients. [9][10][11][12][13] However, most studies comparing neuraxial and general anesthesia have failed to demonstrate a difference in cytokine levels. [9][10][11][12][13] The effect of anesthetic technique for cesarean section on maternal cytokine levels has been studied only minimally.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] However, most studies comparing neuraxial and general anesthesia have failed to demonstrate a difference in cytokine levels. [9][10][11][12][13] The effect of anesthetic technique for cesarean section on maternal cytokine levels has been studied only minimally. 14 The aim of the study was to investigate the effect of neuraxial versus general anesthesia on serum IL-6 and TNF-a levels in healthy parturients undergoing elective cesarean section.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have found similar effects of general and spinal anaesthesia on stress response in patients undergoing surgery. Perioperative levels of TNF, IL-6, CRP are comparable in both types of anaesthesia (Buyukkocak et al, 2006).…”
Section: Regional Anaesthesiamentioning
confidence: 82%